Pup ontogeny and factors influencing behavioural and morphological variation in naked mole-rats, Heterocephalus glaber (Rodentia, Bathyergidae) - O'Riain, Justin (Department of Biological Sciences, 2015)
Bibliography: leaves 151-176.